Journal of Computational Analysis and Applications - SpringerLink (Online service) (New York : Springer US : Imprint: .)
This new peer-reviewed quarterly publishes high-quality research articles from all subareas of computational mathematical analysis. The purpose in bringing together these different branches is to reveal the many potential applications and connections to other areas of mathematical sciences. By working analytically and computationally, the editors believe there will be an increased understanding of important and complex problems of the scientific world. As of 2004, this journal was transferred to Eudoxus Press, LLC. For current volumes, please visit the Publisher's website at http://www.eudoxuspress.com.
Keywords: Harmonic analysis; Approximation theory; Functional analysis; Operator theory; Computer mathematics; Computational Mathematics and Numerical Analysis; Approximations and Expansions; Operator Theory; Abstract Harmonic Analysis; Functional Analysis